Ontological shift in classical criminology: engagement with the new sciences - Milovanovic, Dragan (Critical criminology, 2022)
Advocated is an engagement with the new sciences (quantum mechanics, holography) that challenge Newtonian ontologies. Alternative concepts are introduced suggesting an interconnected, relational, processual, and emergent ontology. Human agency is brought back in the form of an inter- and intra-subjective co-constituted agent, schema QD. Specific applications in criminology are to assemblage theory, cognitive decision-making, methodology, and forms of social control (criminal, restorative, transformative justice).